Efficacy of oral meloxicam suspension for prevention of pain and inflammation following band and surgical castration in calves. Issue 1 (December 2016) - Olson, M.; Ralston, Brenda; Burwash, Les; Matheson-Bird, Heather; Allan, Nick
Abstract Background Castration is one of the most common procedures performed on beef and dairy cattle. The objective of the study was to determine the efficacy of meloxicam oral suspension in reducing pain and inflammation in calves following band or surgical castration. Methods Two identical trials with the exception of the method of castration (Band Castration Study 1 and Surgical Castration Study 2) were conducted. Sixty (60) healthy Holstein calves 4 to 5 months of age (138–202 Kg) were used. Animals received either Meloxicam Oral Suspension at a dose of 1 mg/kg BW (n =  15 Study 1 and 15 Study 2) or Saline (n =  15 Study 1 and 15 Study 2) 2 h before castration. Physiological (Heart Rate, Plasma Cortisol and Plasma Substance P) and Behavioral (Visual Analog Scale (VAS), Accelerometers and tail Pedometers) evaluations were conducted before (day -1) and after Castration (Day 0, 1, 2, 3). Inflammation was evaluated daily by providing an individual animal score (Study1) or with a measurement of scrotal thickness (Study 2). Results Heart rates were significantly greater in control animals following band and surgical castration. Plasma cortisol and substance P were significantly reduced in animals receiving Meloxicam Oral Suspension. Control animals had significantly greater VAS scores. Accelerometers showed that meloxicam treated animals had a significantly greater motion index and number of steps as well as less % time lying and number of lying bouts. The scrotal inflammation (based on scrotal swelling) was significantly decreased in the meloxicam treated animals compared to the control animals on day 1, day 2 and 3. Conclusion Meloxicam Oral Suspension was able to significantly reduce the display of painful behaviors and physiological responses to pain in band castrated and surgical castrated calves for up to 72 h following a single oral treatment of 1 mg/kg body weight. Meloxicam Oral Suspension was able to significantly reduce scrotal inflammation in band castrated and surgical castrated calves.